Design of Digital Aerial Photography System for UAV based on Wireless Sensor Network - Niknamian, Sorush (Yayasan Ahmar Cendekia Indonesia, 2020)
The traditional UAV aerial photography system has the disadvantages of unclear imaging, low system efficiency and poor flight control effect. Thus, a digital aerial photography system based on wireless sensor network is proposed. Firstly, the principle of aerial photography system is analyzed, and the wireless sensor network is set up. A large number of wireless sensor nodes are deployed in the interval, and functions such as wireless communication and calculation are completed by nodes; the SN-RN data acquisition layer, the RN-UAV relay transmission layer and the UAV-DC mobile aggregation layer are designed to form a wireless sensor network architecture, and the UAV digital aerial photography technology is combined to form the wireless sensor network. Experiments show that the medium error, maximum error and medium error limit of the digital aerial photography of the UAV are low, the total working time of the system is short, and the accuracy of the flight execution of the UAV is maintained between 93%-95%, and always stable. Therefore, the overall imaging effect of this method is better, the system work efficiency is higher, the system control effect is better, and it is more practical and advantageous.